Assessing the knowledge and practices of internet of things security and privacy among higher education students - Adamova, Aigul; Zhukabayeva, Tamara; Zhartybayeva, Makpal; Zhumabayeva, Laula (Institute of Advanced Engineering and Science, 2025)
When multiple internet of things (IoT) devices interact, there are risks of privacy breaches, personal data leaks, various attacks, and device manipulation. Security is one of the most important technological research problems that currently exist for the IoT. The main purpose of the present paper is to determine the level of awareness of university students about existing security issues when using IoT devices. The paper presented the methodology of the survey. A questionnaire was developed covering four areas, such as fact-finding about general concepts of the IoT, security measures when using IoT devices, security threats and the presence of vulnerabilities of IoT devices, general policies, practices and shared responsibilities. A methodology for calculating the Awareness Level Index is proposed. This study has potential limitations. The effect estimates in the model are based on a survey of undergraduate and master’s degree students in “Computer Science” and “Software Engineering” within several universities. A total of 370 undergraduate and master’s students participated in the survey. The data processing resulted in the development of recommendations and suggested measures. This study will be useful for both stakeholders and researchers to develop effective strategies and make informed decisions.